A study of the wave impact loads on a fixed column-slab combined structure with a GPU-accelerated SPH method - Zhai, G. (Taylor and Francis Ltd., 2021)
Wave impacts on a semi-submerged platform have a great influence on the structure. Physical experiments and numerical simulations are carried out based on fixed horizontal deck and column-slab combined structures. During the physical experiments, the impact pressures acting on the horizontal decks are measured to verify the accuracy of the numerical models. In the SPH program, by equipping with GPU parallel acceleration processing framework and adopting the dynamic boundary particles method, the total calculation time shortens more than 6 times and the gap near the wavemaker has been eliminated, improving the efficiency and accuracy of numerical calculation significantly. The similarities and differences of the pressure amplitude and distribution between the two structures are summarised and compared. Due to the presence of the columns, the wave energy transmission is largely influenced, and the relationship between the peak pressure and velocity distribution is also demonstrated. The influence of the columns is both considerable and crucial. Â© 2021 Informa UK Limited, trading as Taylor & Francis Group.